The development and delivery of a short, multi-dimensional Study Abroad programme with a twin focus on intercultural skills and employability (Journal of Applied Learning and Teaching, 2020)
This instructional innovation paper reflects on the development and delivery of a short-term Study Abroad programme that responded to twin currents in UK higher education: internationalisation activities that seek to build the competence for negotiating cultural difference and a growing imperative to develop graduate employability for those about to enter a competitive, globalised workplace. Positioned within the literature of experiential learning and global citizenship, the paper outlines the rationale and implementation for an assessment centre approach to programme recruitment as well as a three-phase curriculum comprising (1) online and F2F pre-trip preparation, (2) a week-long study visit to Berlin and (3) a post-visit reflection articulated through critical-reflective writing and a group project exhibit. While the trip to cosmopolitan Berlin offered a useful real-world case study to explore, the main source of intercultural learning was located closer to home in the experience of students working together in project groups of diverse membership.